Strategy Shift Toward Lower Spatial Frequencies in the Recognition of Dynamic Facial Expressions of Basic Emotions: When It Moves It Is Different - Plouffe-Demers, Marie-Pier; Fiset, Daniel; Saumure, Camille; Duncan, Justin; Blais, Caroline (Frontiers in Psychology, 2019)
Facial expressions of emotion play a key role in social interactions. While in everyday life, their dynamic and transient nature calls for a fast processing of the visual information they contain, a majority of studies investigating the visual processes underlying their recognition have focused on their static display. The present study aimed to gain a better understanding of these processes while using more ecological dynamic facial expressions. In two experiments, we directly compared the spatial frequency (SF) tuning during the recognition of static and dynamic facial expressions. Experiment 1 revealed a shift towards lower SFs for dynamic expressions in comparison to static ones. In Experiment 2, we tested the hypothesis that biological motion may explain the reliance on lower SF content by comparing the SF tuning profiles of static, dynamic, and shuffled expressions. Results showed a similar shift toward lower SFs for shuffled expressions, suggesting that the difference found between dynamic and static expressions might not be linked to biological motion per se but to the presence of motion regardless its nature.